A directional heat-conducting composite phase-change material and a preparation method thereof
By using the technology of directional thermal conduction composite phase change materials in thermal interface composite materials, using the combination of graphite sheets and cotton cloth, combined with the design of adhesive layer, the problem of low thermal conductivity of existing thermal conductivity materials is solved, and efficient and economical thermal conductivity is achieved, which is suitable for the heat dissipation needs of electronic equipment.
Patent Information
- Application Number
- CN202211283848.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-19
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-10-19
AI Technical Summary
The thermal conductivity efficiency in existing thermal interface composite thermal conductivity materials is not high and the orientation process is complex, which makes it difficult to achieve high thermal conductivity, especially when the heat dissipation demand in electronic devices increases.
Using a directional thermal conduction composite phase change material, a continuous graphite layer is formed by adsorbing the graphite sheet suspension onto a cotton cloth and rolling it to form a continuous graphite layer. Combined with the use of the adhesive layer, a porous directional thermal conduction matrix is constructed and a phase change material is filled therein to achieve directional thermal conduction characteristics.
It realizes the oriented thermal conduction composite materials with high thermal conductivity at a lower filler ratio and cost, which is suitable for the efficient heat dissipation needs of electronic devices, and simplifies the preparation process and reduces costs.
Smart Images

Figure CN115595122B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat-conducting materials, and in particular to a directional heat-conducting composite phase-change material and a preparation method thereof. Background Art
[0002] With the rapid development of modern microelectronics technology, electronic devices have become ultra-thin and lightweight, but the power of the devices has become increasingly larger, resulting in a significant increase in unit power density. The heat generated during operation is not easy to discharge, and the accumulation of heat will reduce the performance and service life of electronic devices. What's more, it will cause thermal runaway of electronic devices and affect the personal safety of users. Therefore, the current electronics industry has put forward higher and higher requirements on the heat dissipation materials of heat-generating core components, and urgently needs a highly efficient thermally conductive and lightweight material to quickly transfer heat to ensure the normal operation of electronic equipment.
[0003] The traditional heat transfer method of thermal management material systems is to conduct heat from the point of generation to the surface of the heat sink. However, as the size of electronic devices continues to shrink, the porosity of the contact interface between the thermal management material system and the packaging shell gradually increases. The pores between the interfaces at the microscale have a great impact on the heat conduction of the thermal management system. In order to reduce the interfacial thermal resistance as much as possible, interface materials are introduced between power components such as chips and the heat sink interface to fill their air pores.
[0004] In order to ensure the long-term stability of electronic devices, thermal interface materials not only have requirements for thermal conductivity, but also must meet certain standards in terms of pore filling, temperature control stability, etc. Phase change thermal interface composite materials have become one of the most promising thermal interface materials due to their good pore filling, phase change temperature control, corrosion resistance, and easy processing. However, the thermal conductivity of most phase change materials is very low. When used, phase change materials are often used as the matrix, and high thermal conductivity fillers are added to increase the thermal conductivity of the thermal interface composite phase change material.
[0005] As is known to all, the thermal conductivity of anisotropic high thermal conductive fillers in the axial or in-plane direction can reach hundreds of W / mk, such as carbon fibers and carbon nanotubes with one-dimensional structures, and boron nitride, graphite sheets, graphene, etc. with two-dimensional structures. If these anisotropic high thermal conductive fillers can be oriented in a phase change material, the thermal conductive material can have a higher thermal conductivity in a specific direction, which is beneficial for heat conduction and heat dissipation along a specific direction. However, the orientation process of existing thermal conductive fillers is not highly oriented or the orientation process is relatively complicated, and a higher filler ratio or a higher cost is required to obtain a high thermal conductivity. Therefore, it is necessary to provide a thermal interface composite thermal conductive material that can achieve higher thermal conductivity at a lower filler ratio and a lower cost. Summary of the invention
[0006] The present invention aims to solve the technical problems of low thermal conductivity in existing thermal interface composite thermal conductive materials. To this end, the present invention proposes a directional thermal conductive composite phase change material and a preparation method thereof that can achieve high thermal conductivity with a low filler ratio and low cost.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A directional heat-conducting composite phase-change material comprises a graphite layer, a cotton cloth, an adhesive layer and a phase-change material. The cotton cloth is a cloth carrier impregnated with graphite flake powder; the graphite layers are symmetrically distributed on both sides of the cotton cloth, and the cotton cloth and the graphite layers constitute a heat-conducting cloth; the adhesive layer is evenly coated on both sides of the heat-conducting cloth, and a plurality of layers of heat-conducting cloth are adhered and stacked to form a porous directional heat-conducting matrix; the phase-change material is impregnated in the above-mentioned directional porous heat-conducting matrix, thereby forming a directional heat-conducting composite phase-change material.
[0009] Preferably, the thickness of the cotton cloth in the directional heat-conducting composite phase change material is 50-1000 μm, and the material thereof is cotton cellulose or wood cellulose.
[0010] Preferably, the thickness of the graphite layer in the directional heat-conducting composite phase-change material is 1 to 200 μm.
[0011] Preferably, the adhesive in the directional heat-conducting composite phase-change material may be selected from polyvinyl acetate emulsion, bisphenol A epoxy resin adhesive, acrylate adhesive, and polyurethane adhesive, and the thickness thereof is 1 to 200 μm.
[0012] Preferably, the phase change material in the directional heat-conducting composite phase change material is higher aliphatic hydrocarbons, fatty acids, esters, and crystalline hydrated salts.
[0013] The present invention also provides a method for preparing a directional heat-conducting composite phase-change material according to the above technical solution, comprising the following steps:
[0014] (1) placing cotton in an alkaline solution and heating it for degreasing;
[0015] (2) ultrasonically dispersing graphite flake powder in a predetermined binder solution to form a graphite flake suspension;
[0016] (3) The degreased cotton cloth of step (1) is immersed in the graphite flake suspension of step (2), and the graphite flakes are evenly immersed and dispersed on the cotton cloth through repeated immersion.
[0017] (4) After drying the cotton cloth with the graphite sheet attached in step (3), spraying anhydrous ethanol on the surface of the cotton cloth with the graphite sheet attached to wet it, and rolling it using a stainless steel roller and a roller press, so that the graphite sheet is closely attached to the cotton cloth and a graphite layer is formed on both sides of the cotton cloth to make a thermal conductive cloth;
[0018] (5) applying adhesive to the surface of the heat-conducting fabric obtained in step (4), adhering and stacking several layers of the heat-conducting fabric, and pressing them to form a layered porous directional heat-conducting substrate;
[0019] (6) Using a vacuum impregnation method, the phase change material is impregnated into the layered porous directional heat conducting matrix obtained in step (5) to obtain a composite phase change material having directional heat conducting properties.
[0020] Preferably, in the method for preparing the directional heat-conducting composite phase-change material, the predetermined binder in step (2) is selected as polyvinylidene fluoride (PVDF), the corresponding solvent is dimethylformamide (DMF), the corresponding solvent of polyacrylonitrile (PAN) is dimethylformamide (DMF), the corresponding solvent of polyamide (PA) is N-methylpyrrolidone (NMP), the corresponding solvent of polyvinylpyrrolidone (PVP) is ethanol, the corresponding solvent of polyacrylic acid (PAA) is ethanol, the corresponding solvent of sodium carboxymethyl cellulose (CMC) is water, and the corresponding solvent of polyvinyl alcohol (PVA) is water; the concentration of the binder solution is 1 to 5 wt%.
[0021] Preferably, in the method for preparing the directional heat-conducting composite phase-change material, the graphite sheets in step (3) account for 15-50 wt % of the heat-conducting fabric.
[0022] The beneficial effects of the present invention are as follows:
[0023] 1. The present invention utilizes the good adsorption performance of cotton cloth to adsorb the graphite sheet suspension in the cotton cloth. After rolling, a continuous graphite layer is formed on the surface of the cotton cloth. The graphite layer has a higher thermal conductivity, and a thermally conductive cloth with high thermal conductivity along the in-plane direction is made; a plurality of layers of thermally conductive cloth are adhered and stacked through an adhesive layer to form a porous directional thermally conductive matrix, and the adhesive layer has a low thermal conductivity, which can hinder the heat from propagating along the normal direction of the thermally conductive cloth, thereby forming a porous matrix with directional thermally conductive properties; after filling the thermally conductive matrix with a phase change material, a directional thermally conductive phase change composite material is made. The composite material has the characteristics of highly directional thermally conductive and can achieve higher thermal conductivity with a lower proportion of anisotropic thermally conductive fillers. The directional thermally conductive phase change composite material prepared by the present invention can further adapt to the heat dissipation needs brought about by the rapid development of electronic devices.
[0024] 2. The preparation method of the present invention is simple and has low process cost. The obtained directional heat-conducting composite phase-change material exhibits excellent thermal conductivity and is easy to industrialize and mass-produce.
[0025] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0027] Figure 1 (a) is a photo of the rolled thermal conductive fabric in Example 1; Figure 1 (b) is a physical picture of the thermal conductive fabric prepared in Example 1;
[0028] Figure 2 Schematic diagram of cotton cloth with attached graphite layer. In the figure, 1-cotton cloth; 2-graphite sheet, i.e., graphite sheet impregnated inside the cotton cloth; 3-graphite layer, which is the graphite layer formed after the graphite sheet is pressed on the surface of the cotton cloth.
[0029] Figure 3 (a) is the SEM image of graphite distribution on the surface of thermal conductive fabric; Figure 3 (b) is the SEM image of the distribution of graphite flakes inside the thermal conductive fabric.
[0030] Figure 4 (a) is a schematic diagram of the structure of a porous directional heat-conducting substrate, in which 1 is heat-conducting fabric, 2 is adhesive layer, 3 is the direction of high thermal conductivity for directional heat conduction, and 4 is the direction of low thermal conductivity. Figure 4 (b) is a schematic diagram of a directional heat-conducting composite phase change material, where 1 is a phase change material, i.e., a phase change material impregnated in a porous heat-conducting matrix.
[0031] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0032] Embodiment 1:
[0033] 1. Preparation of composite materials with oriented and ordered assembled graphite layers on cotton cloth surface
[0034] (1) Pretreatment of cotton cloth: 6 pieces of cotton cloth (thickness 200 μm) with a size of 5×60 cm were cut out and weighed about 25 g. The cotton cloth was boiled in a 5 wt% NaOH solution for 2 h to remove impurities and lignin in the cotton cloth. After washing and drying, the remaining mass was about 23.5 g.
[0035] (2) Dispersion of graphite flakes: First, take 3 pieces (11.75 g) of the treated cotton cloth, and weigh 2.94 g of graphite flakes (particle size 10-20 μm, number of layers 1 to 10) based on the ratio of graphite flakes to the thermal conductive fabric being 25 wt%. Then, prepare a 1 wt% PVDF solution using N,N-dimethylformamide (DMF) as a solvent and polyvinylidene fluoride (PVDF) as a binder. Finally, evenly disperse a certain amount of graphite flakes in the PVDF solution.
[0036] (3) Directed and orderly assembly of graphite layers on the surface of cotton cloth: the cotton cloth degreased in step (1) is immersed in the graphite flake suspension in step (2), and after repeated immersion, the graphite flakes are evenly dispersed on the cotton cloth.
[0037] The above steps can ensure that the graphite sheets are evenly dispersed on the cotton cloth to form a thermally conductive cloth.
[0038] (4) The thermal conductive fabric in step (3) is dried, and then sprayed with anhydrous ethanol to wet the thermal conductive fabric, and then the graphite sheet attached to the cotton cloth is rolled by a stainless steel cylinder to initially roll the graphite sheet into a continuous graphite layer. Finally, the thermal conductive fabric is replaced with a roller press for pressing. The pressing process is as follows: Figure 1 (a) is shown. The final physical picture of the repeatedly pressed thermal conductive fabric is shown in Figure 1 As shown in (b), it can be seen from the figure that the graphite flakes are evenly distributed on the cotton cloth, and a graphite layer is attached to it. In order to observe the distribution of graphite flakes on the cotton cloth more clearly, we conducted a microscopic morphology observation on the thermal conductive fabric. Figure 3 As shown in (a), the graphite sheets are evenly and orientedly distributed on the cotton cloth, and the graphite sheets form a whole. Figure 3 In (b), it can be observed that the graphite flakes are also embedded in the fiber gaps inside the cotton cloth, so there is a strong adhesion between the graphite layer and the cotton cloth.
[0039] 2. Preparation of directional heat conducting composite materials
[0040] First, cut 30 pieces of 5×5cm thermal conductive fabric from the pressed thermal conductive fabric, and brush polyvinyl acetate emulsion on the surface of the thermal conductive fabric with a thickness of about 50μm. After the 30 pieces of thermal conductive fabric are adhered and stacked, they are pressed to form a layered porous directional thermal conductive substrate.
[0041] 3. Preparation of paraffin phase change materials and oriented composite materials
[0042] 60g of paraffin was placed in a beaker and heated to 80°C to completely melt it. Next, the directional heat-conducting composite material was immersed in liquid paraffin to completely immerse it in the paraffin, and then kept at a constant temperature of 70°C for 4 hours in a vacuum device, the sample was removed, and cooled to room temperature to obtain a directional heat-conducting phase change composite material.
[0043] Embodiment 2:
[0044] 1. Preparation of composite materials with oriented and ordered assembled graphite layers on cotton cloth surface
[0045] (1) Pretreatment of cotton cloth: 6 pieces of cotton cloth (200 μm thick) with a size of 5×60 cm were cut and weighed about 25 g. The cotton cloth was boiled in a 5 wt% NaOH solution for 2 h to remove impurities and lignin in the cotton cloth. After washing and drying, the remaining mass was about 23.5 g.
[0046] (2) Dispersion of graphite flakes: First, take 3 pieces (11.75 g) of treated cotton cloth and weigh 1.76 g of graphite flakes (particle size 10-20 μm, number of layers 1 to 10) according to the ratio of graphite flakes to the thermal conductive cloth of 15 wt%. Secondly, prepare a 1 wt% PAN solution with polyacrylonitrile (PAN) as a binder and dimethylformamide (DMF) as a solvent. Finally, disperse a certain amount of graphite flakes in the PAN solution.
[0047] (3) Directed and orderly assembly of graphite layers on the surface of cotton cloth: the cotton cloth degreased in step (1) is immersed in the graphite flake suspension in step (2), and after repeated immersion, the graphite flakes are evenly dispersed on the cotton cloth.
[0048] The above steps can ensure that the graphite sheets are evenly dispersed on the cotton cloth to form a thermally conductive cloth.
[0049] (4) The thermal conductive fabric in step (3) is dried, and then sprayed with anhydrous ethanol to wet the thermal conductive fabric, and then the graphite sheet attached to the cotton cloth is rolled by a stainless steel cylinder to initially roll the graphite sheet into a continuous graphite layer. Finally, the thermal conductive fabric is replaced with a roller press for pressing.
[0050] 2. Preparation of directional heat conducting composite materials
[0051] First, cut 30 pieces of 5×5cm thermal conductive fabric from the pressed thermal conductive fabric, and brush bisphenol A epoxy resin glue on the surface of the thermal conductive fabric with a thickness of about 50μm. After the 30 pieces of thermal conductive fabric are adhered and stacked, they are pressed to form a layered porous directional thermal conductive substrate.
[0052] 3. Preparation of stearic acid phase change materials and oriented composite materials
[0053] 60g of stearic acid was placed in a beaker and heated to 100°C to completely melt it. Next, the directional heat-conducting composite material was immersed in liquid stearic acid to completely immerse it in the stearic acid, and then kept at a constant temperature of 80°C for 4 hours in a vacuum device, the sample was removed, and cooled to room temperature to obtain a directional phase change composite material.
[0054] Embodiment 3:
[0055] 1. Preparation of composite materials with oriented and ordered assembled graphite layers on cotton cloth surface
[0056] (1) Pretreatment of cotton cloth: 6 pieces of cotton cloth (thickness 200 μm) with a size of 5×60 cm were cut out and weighed about 25 g. The cotton cloth was boiled in a 5 wt% NaOH solution for 2 h to remove impurities and lignin in the cotton cloth. After washing and drying, the remaining mass was about 23.5 g.
[0057] (2) Dispersion of graphite flakes: First, take 3 pieces (11.75 g) of treated cotton cloth and weigh 5.88 g of graphite flakes (particle size 10-20 μm, number of layers 1 to 10) according to the ratio of graphite flakes to the thermal conductive cloth of 50 wt%. Secondly, prepare a 1 wt% PA solution with polyamide (PA) as a binder and N-methylpyrrolidone (NMP) as a solvent. Finally, disperse a certain amount of graphite flakes in the PA solution.
[0058] (3) Directed and orderly assembly of graphite layers on the surface of cotton cloth: the cotton cloth degreased in step (1) is immersed in the graphite flake suspension in step (2), and after repeated immersion, the graphite flakes are evenly dispersed on the cotton cloth.
[0059] The above steps can ensure that the graphite sheets are evenly dispersed on the cotton cloth to form a thermally conductive cloth.
[0060] (4) The thermal conductive fabric in step (3) is dried, and then sprayed with anhydrous ethanol to wet the thermal conductive fabric, and then the graphite sheet attached to the cotton cloth is rolled by a stainless steel cylinder to initially roll the graphite sheet into a continuous graphite layer. Finally, the thermal conductive fabric is replaced with a roller press for pressing.
[0061] 2. Preparation of directional heat conducting composite materials
[0062] First, cut 30 pieces of 5×5cm thermal conductive fabric from the pressed thermal conductive fabric, and apply acrylic glue on the surface of the thermal conductive fabric with a thickness of about 50μm. After the 30 pieces of thermal conductive fabric are adhered and stacked, they are pressed to form a layered porous directional thermal conductive substrate.
[0063] 3. Preparation of fatty acid phase change materials and oriented composite materials
[0064] 60g of fatty acid was placed in a beaker and heated to 80°C to completely melt it. Next, the directional heat-conducting composite material was immersed in liquid fatty acid to completely immerse it in the fatty acid, and then kept at a constant temperature of 70°C in a vacuum device for 4 hours, the sample was removed, and cooled to room temperature to obtain a directional heat-conducting phase change composite material.
[0065] Embodiment 4:
[0066] 1. Preparation of composite materials with oriented and ordered assembled graphite layers on cotton cloth surface
[0067] (1) Pretreatment of cotton cloth: 6 pieces of cotton cloth (thickness 200 μm) with a size of 5×60 cm were cut out and weighed about 25 g. The cotton cloth was boiled in a 5 wt% NaOH solution for 2 h to remove impurities and lignin in the cotton cloth. After washing and drying, the remaining mass was about 23.5 g.
[0068] (2) Dispersion of graphite flakes: First, take 3 pieces (11.75 g) of the treated cotton cloth, weigh 2.93 g of graphite flakes (particle size 10-20 μm, number of layers 1 to 10) based on the ratio of graphite flakes to the thermal conductive fabric of 25 wt%. Next, prepare a 5 wt% solution of PVP using polyvinyl pyrrolidone (PVP) as a binder and ethanol as a solvent. Finally, disperse a certain amount of graphite flakes in the PVP solution.
[0069] (3) Directed and orderly assembly of graphite layers on the surface of cotton cloth: the cotton cloth degreased in step (1) is immersed in the graphite flake suspension in step (2), and after repeated immersion, the graphite flakes are evenly dispersed on the cotton cloth.
[0070] The above steps can ensure that the graphite sheets are evenly dispersed on the cotton cloth to form a thermally conductive cloth.
[0071] (4) The thermal conductive fabric in step (3) is dried, and then sprayed with anhydrous ethanol to wet the thermal conductive fabric, and then the graphite sheet attached to the cotton cloth is rolled by a stainless steel cylinder to initially roll the graphite sheet into a continuous graphite layer. Finally, the thermal conductive fabric is replaced with a roller press for pressing.
[0072] 2. Preparation of directional heat conducting composite materials
[0073] First, cut 30 pieces of 5×5cm thermal conductive fabric from the pressed thermal conductive fabric, and brush the surface of the thermal conductive fabric with polyurethane adhesive to a thickness of about 50μm. After the 30 pieces of thermal conductive fabric are adhered and stacked, they are pressed to form a layered porous directional thermal conductive substrate.
[0074] 3. Preparation of sodium acetate trihydrate phase change materials and oriented composite materials
[0075] Take 60g of sodium acetate trihydrate and 1.2g of disodium hydrogen phosphate dodecahydrate and put them in a beaker, heat them to 80℃, melt them completely and mix them evenly. Secondly, slowly add 0.3g of carboxymethyl cellulose to the mixed liquid and stir it thoroughly to dissolve it. Finally, immerse the directional heat-conducting composite material into the modified liquid sodium acetate trihydrate so that it is completely immersed in the solution, then keep it at a constant temperature of 70℃ for 4h in a vacuum device, remove the sample, and cool it to room temperature to obtain a directional phase change composite material.
[0076] Embodiment 5:
[0077] 1. Preparation of composite materials with oriented and ordered assembled graphite layers on cotton cloth surface
[0078] (1) Pretreatment of cotton cloth: 24 pieces of cotton cloth (50 μm thick) with a size of 5×60 cm were cut out and weighed about 25 g. The cotton cloth was boiled in a 5 wt% NaOH solution for 2 h to remove impurities and lignin in the cotton cloth. After washing and drying, the remaining mass was about 23.5 g.
[0079] (2) Dispersion of graphite flakes: First, take 12 pieces (11.75 g) of the treated cotton cloth, and weigh 1.76 g of graphite flakes (particle size 10-20 μm, number of layers 1 to 10) according to the ratio of graphite flakes to the thermal conductive fabric of 15 wt%. Then, prepare a 1 wt% PVDF solution with N, N-dimethylformamide (DMF) as solvent. Finally, evenly disperse a certain amount of graphite flakes in the PVDF solution.
[0080] (3) Directed and orderly assembly of graphite layers on the surface of cotton cloth: the cotton cloth degreased in step (1) is immersed in the graphite flake suspension in step (2), and after repeated immersion, the graphite flakes are evenly dispersed on the cotton cloth.
[0081] The above steps can ensure that the graphite sheets are evenly dispersed on the cotton cloth to form a thermally conductive cloth.
[0082] (4) The thermal conductive fabric in step (3) is dried, and then sprayed with anhydrous ethanol to wet the thermal conductive fabric, and then the graphite sheet attached to the cotton cloth is rolled by a stainless steel cylinder to initially roll the graphite sheet into a continuous graphite layer. Finally, the thermal conductive fabric is replaced with a roller press for pressing.
[0083] 2. Preparation of directional heat conducting composite materials
[0084] First, cut the pressed thermal conductive fabric into 120 pieces of 5×5cm in size, and brush the surface of the thermal conductive fabric with polyvinyl acetate emulsion to a thickness of about 1μm. After the 120 pieces of thermal conductive fabric are adhered and stacked, they are pressed to form a layered porous directional thermal conductive substrate.
[0085] 3. Preparation of paraffin phase change materials and oriented composite materials
[0086] 60g of paraffin was placed in a beaker and heated to 80°C to completely melt it. Next, the directional heat-conducting composite material was immersed in liquid paraffin to completely immerse it in the paraffin, and then kept at a constant temperature of 70°C for 4 hours in a vacuum device, the sample was removed, and cooled to room temperature to obtain a directional heat-conducting phase change composite material.
[0087] Embodiment 6:
[0088] 1. Preparation of composite materials with oriented and ordered assembled graphite layers on cotton cloth surface
[0089] (1) Pretreatment of cotton cloth: 24 pieces of cotton cloth (50 μm thick) with a size of 5×60 cm were cut out and weighed about 25 g. The cotton cloth was boiled in a 5 wt% NaOH solution for 2 h to remove impurities and lignin in the cotton cloth. After washing and drying, the remaining mass was about 23.5 g.
[0090] (2) Dispersion of graphite flakes: First, take 12 pieces (11.75 g) of the treated cotton cloth and weigh 2.93 g of graphite flakes (particle size 10-20 μm, number of layers 1 to 10) according to the ratio of graphite flakes to the thermal conductive fabric of 25 wt%. Secondly, prepare a 1 wt% PAN solution using polyacrylonitrile (PAN) as a binder and dimethylformamide (DMF) as a solvent. Finally, disperse a certain amount of graphite flakes in the PAN solution.
[0091] (3) Directed and orderly assembly of graphite layers on the surface of cotton cloth: the cotton cloth degreased in step (1) is immersed in the graphite flake suspension in step (2), and after repeated immersion, the graphite flakes are evenly dispersed on the cotton cloth.
[0092] The above steps can ensure that the graphite sheets are evenly dispersed on the cotton cloth to form a thermally conductive cloth.
[0093] (4) The thermal conductive fabric in step (3) is dried, and then sprayed with anhydrous ethanol to wet the thermal conductive fabric, and then the graphite sheet attached to the cotton cloth is rolled by a stainless steel cylinder to initially roll the graphite sheet into a continuous graphite layer. Finally, the thermal conductive fabric is replaced with a roller press for pressing.
[0094] 2. Preparation of directional heat conducting composite materials
[0095] First, cut the pressed thermal conductive fabric into 120 pieces of 5×5cm in size, and brush bisphenol A epoxy resin glue on the surface of the thermal conductive fabric with a thickness of about 1μm. After the 120 pieces of thermal conductive fabric are adhered and stacked, they are pressed to form a layered porous directional thermal conductive substrate.
[0096] 3. Preparation of stearic acid phase change materials and oriented composite materials
[0097] 60g of stearic acid was placed in a beaker and heated to 80°C to completely melt it. Next, the directional heat-conducting composite material was immersed in liquid stearic acid to completely immerse it in the stearic acid, and then kept at a constant temperature of 70°C for 4 hours in a vacuum device, the sample was removed, and cooled to room temperature to obtain a directional heat-conducting phase change composite material.
[0098] Embodiment 7:
[0099] 1. Preparation of composite materials with oriented and ordered assembled graphite layers on cotton cloth surface
[0100] (1) Pretreatment of cotton cloth: Two pieces of cotton cloth (1000 μm thick) with a size of 5×30 cm were cut and weighed about 25 g. The cotton cloth was boiled in a 5 wt% NaOH solution for 2 h to remove impurities and lignin in the cotton cloth. After washing and drying, the remaining mass was about 23.5 g.
[0101] (2) Dispersion of graphite flakes: First, take one piece of treated cotton cloth (11.75 g), and weigh 5.87 g of graphite flakes (particle size 10-20 μm, number of layers 1 to 10) according to the ratio of graphite flakes to the thermal conductive fabric of 50 wt%. Secondly, prepare a 1 wt% PA solution using polyamide (PA) as a binder and N-methylpyrrolidone (NMP) as a solvent. Finally, disperse a certain amount of graphite flakes in the PA solution.
[0102] (3) Directed and orderly assembly of graphite layers on the surface of cotton cloth: the cotton cloth degreased in step (1) is immersed in the graphite flake suspension in step (2), and after repeated immersion, the graphite flakes are evenly dispersed on the cotton cloth.
[0103] The above steps can ensure that the graphite sheets are evenly dispersed on the cotton cloth to form a thermally conductive cloth.
[0104] (4) The thermal conductive fabric in step (3) is dried, and then sprayed with anhydrous ethanol to wet the thermal conductive fabric, and then the graphite sheet attached to the cotton cloth is rolled by a stainless steel cylinder to initially roll the graphite sheet into a continuous graphite layer. Finally, the thermal conductive fabric is replaced with a roller press for pressing.
[0105] 2. Preparation of directional heat conducting composite materials
[0106] First, cut the pressed thermal conductive fabric into 12 pieces of 5×5 cm in size, and apply acrylic glue on the surface of the thermal conductive fabric with a brush to a thickness of about 200 μm. After the 12 pieces of thermal conductive fabric are adhered and stacked, they are pressed to form a layered porous directional thermal conductive substrate.
[0107] 3. Preparation of fatty acid phase change materials and oriented composite materials
[0108] 60g of fatty acid was placed in a beaker and heated to 80°C to completely melt it. Next, the directional heat-conducting composite material was immersed in the liquid fatty acid to completely immerse it in the fatty acid, and then kept at a constant temperature of 70°C for 4 hours in a vacuum device, the sample was removed, and cooled to room temperature to obtain a directional heat-conducting phase change composite material.
[0109] Embodiment 8:
[0110] 1. Preparation of composite materials with oriented and ordered assembled graphite layers on cotton cloth surface
[0111] (1) Pretreatment of cotton cloth: Two pieces of cotton cloth (1000 μm thick) with a size of 5×60 cm were cut and weighed about 25 g. The cotton cloth was boiled in a 5 wt% NaOH solution for 2 h to remove impurities and lignin in the cotton cloth. After washing and drying, the remaining mass was about 23.5 g.
[0112] (2) Dispersion of graphite flakes: First, take one piece of treated cotton cloth (11.75 g), and weigh 2.93 g of graphite flakes (particle size 10-20 μm, number of layers 1 to 10) according to the ratio of graphite flakes to the thermal conductive fabric of 25 wt%. Secondly, prepare a 5 wt% solution of PVP with polyvinyl pyrrolidone (PVP) as a binder and ethanol as a solvent. Finally, disperse a certain amount of graphite flakes in the PVP solution.
[0113] (3) Directed and orderly assembly of graphite layers on the surface of cotton cloth: the cotton cloth degreased in step (1) is immersed in the graphite flake suspension in step (2), and after repeated immersion, the graphite flakes are evenly dispersed on the cotton cloth.
[0114] The above steps can ensure that the graphite sheets are evenly dispersed on the cotton cloth to form a thermally conductive cloth.
[0115] (4) The thermal conductive fabric in step (3) is dried, and then sprayed with anhydrous ethanol to wet the thermal conductive fabric, and then the graphite sheet attached to the cotton cloth is rolled by a stainless steel cylinder to initially roll the graphite sheet into a continuous graphite layer. Finally, the thermal conductive fabric is replaced with a roller press for pressing.
[0116] 2. Preparation of directional heat conducting composite materials
[0117] First, cut the pressed thermal conductive fabric into 12 pieces of 5×5cm in size, and apply polyurethane adhesive on the surface of the thermal conductive fabric with a brush to a thickness of about 200μm. After the 12 pieces of thermal conductive fabric are adhered and stacked, they are pressed to form a layered porous directional thermal conductive substrate.
[0118] 3. Preparation of sodium acetate trihydrate phase change materials and oriented composite materials
[0119] Take 60g of sodium acetate trihydrate and 1.2g of disodium hydrogen phosphate dodecahydrate and put them in a beaker, heat them to 80°C, melt them completely and mix them evenly. Secondly, slowly add 0.3g of carboxymethyl cellulose to the mixed liquid above and stir it thoroughly to dissolve it. Finally, immerse the directional heat-conducting composite material into the modified liquid sodium acetate trihydrate so that it is completely immersed in the liquid, then keep it at a constant temperature of 70°C in a vacuum device for 4 hours, remove the sample, and cool it to room temperature to obtain a directional heat-conducting phase change composite material.
[0120] Embodiment 9:
[0121] 1. Preparation of composite materials with oriented and ordered assembled graphite layers on cotton cloth surface
[0122] (1) Pretreatment of cotton cloth: Two pieces of cotton cloth (200 μm thick) with a size of 5×60 cm were cut and weighed about 25 g. The cotton cloth was boiled in a 5 wt% NaOH solution for 2 h to remove impurities and lignin in the cotton cloth. After washing and drying, the remaining mass was about 23.5 g.
[0123] (2) Dispersion of graphite flakes: First, take one piece of treated cotton cloth (11.75 g), and weigh 1.76 g of graphite flakes (particle size 10-20 μm, number of layers 1 to 10) according to the ratio of graphite flakes to the thermal conductive fabric of 15 wt%. Secondly, polyacrylic acid (PAA) is used as a binder, and ethanol is used as a solvent to prepare a 5 wt% PAA solution. Finally, a certain amount of graphite flakes are dispersed in the PAA solution.
[0124] (3) Directed and orderly assembly of graphite layers on the surface of cotton cloth: the cotton cloth degreased in step (1) is immersed in the graphite flake suspension in step (2), and after repeated immersion, the graphite flakes are evenly dispersed on the cotton cloth.
[0125] The above steps can ensure that the graphite sheets are evenly dispersed on the cotton cloth to form a thermally conductive cloth.
[0126] (4) The thermal conductive fabric in step (3) is dried, and then sprayed with anhydrous ethanol to wet the thermal conductive fabric, and then the graphite sheet attached to the cotton cloth is rolled by a stainless steel cylinder to initially roll the graphite sheet into a continuous graphite layer. Finally, the thermal conductive fabric is replaced with a roller press for pressing.
[0127] 2. Preparation of directional heat conducting composite materials
[0128] First, cut the pressed thermal conductive fabric into 12 pieces of 5×5cm in size, and brush the surface of the thermal conductive fabric with polyurethane adhesive to a thickness of about 200μm. After the 12 pieces of thermal conductive fabric are adhered and stacked, they are pressed to form a layered porous directional thermal conductive substrate.
[0129] 3. Preparation of sodium sulfate decahydrate phase change material and oriented composite material
[0130] Take 60g of sodium sulfate decahydrate and 1.2g of disodium hydrogen phosphate dodecahydrate and put them in a beaker, heat to 80°C, melt them completely and mix them evenly. Secondly, slowly add 0.3g of carboxymethyl cellulose to the mixed liquid above and stir it thoroughly to dissolve it. Finally, immerse the preparation of the directional composite material in the modified liquid sodium sulfate decahydrate so that it is completely immersed in the liquid, then keep it at a constant temperature of 70°C in a vacuum device for 4 hours, remove the sample, and cool it to room temperature to obtain the preparation of the directional thermal conductive phase change composite material.
[0131] Embodiment 10:
[0132] 1. Preparation of composite materials with oriented and ordered assembled graphite layers on cotton cloth surface
[0133] (1) Pretreatment of cotton cloth: 6 pieces of cotton cloth (thickness 200 μm) with a size of 5×60 cm were cut out and weighed about 25 g. The cotton cloth was boiled in a 5 wt% NaOH solution for 2 h to remove impurities and lignin in the cotton cloth. After washing and drying, the remaining mass was about 23.5 g.
[0134] (2) Dispersion of graphite flakes: First, take 3 pieces (11.75 g) of the treated cotton cloth, and weigh 2.94 g of graphite flakes (particle size 10-20 μm, number of layers 1 to 10) based on the ratio of graphite flakes to the thermal conductive cloth of 25 wt%. Then, prepare a 2 wt% solution of carboxymethyl cellulose (CMC) using water as solvent and sodium carboxymethyl cellulose (CMC) as binder. Finally, evenly disperse a certain amount of graphite flakes in the CMC solution.
[0135] (3) Directed and orderly assembly of graphite layers on the surface of cotton cloth: the cotton cloth degreased in step (1) is immersed in the graphite flake suspension in step (2), and after repeated immersion, the graphite flakes are evenly dispersed on the cotton cloth.
[0136] The above steps can ensure that the graphite sheets are evenly dispersed on the cotton cloth to form a thermally conductive cloth.
[0137] (4) The thermal conductive fabric in step (3) is dried, and then sprayed with anhydrous ethanol to wet the thermal conductive fabric, and then the graphite sheet attached to the cotton cloth is rolled by a stainless steel cylinder to initially roll the graphite sheet into a continuous graphite layer. Finally, the thermal conductive fabric is replaced with a roller press for pressing. The pressing process is as follows: Figure 1 (a) is shown. The final physical picture of the repeatedly pressed thermal conductive fabric is shown in Figure 1As shown in (b), it can be seen from the figure that the graphite flakes are evenly distributed on the cotton cloth, and a graphite layer is attached to it. In order to observe the distribution of graphite flakes on the cotton cloth more clearly, we conducted a microscopic morphology observation on the thermal conductive fabric. Figure 3 As shown in (a), the graphite sheets are evenly and oriented on the cotton cloth, and the graphite sheets form a whole. Figure 3 In (b), it can be observed that the graphite flakes are also embedded in the fiber gaps inside the cotton cloth, so there is a strong adhesion between the graphite layer and the cotton cloth.
[0138] 2. Preparation of directional heat conducting composite materials
[0139] First, cut 30 pieces of 5×5cm thermal conductive fabric from the pressed thermal conductive fabric, and brush polyvinyl acetate emulsion on the surface of the thermal conductive fabric with a thickness of about 50μm. After the 30 pieces of thermal conductive fabric are adhered and stacked, they are pressed to form a layered porous directional thermal conductive substrate.
[0140] 3. Preparation of paraffin phase change materials and oriented composite materials
[0141] 60g of paraffin was placed in a beaker and heated to 80°C to completely melt it. Next, the directional heat-conducting composite material was immersed in liquid paraffin to completely immerse it in the paraffin, and then kept at a constant temperature of 70°C for 4 hours in a vacuum device, the sample was removed, and cooled to room temperature to obtain a directional heat-conducting phase change composite material.
[0142] Embodiment 11:
[0143] 1. Preparation of composite materials with oriented and ordered assembled graphite layers on cotton cloth surface
[0144] (1) Pretreatment of cotton cloth: 6 pieces of cotton cloth (200 μm thick) with a size of 5×60 cm were cut and weighed about 25 g. The cotton cloth was boiled in a 5 wt% NaOH solution for 2 h to remove impurities and lignin in the cotton cloth. After washing and drying, the remaining mass was about 23.5 g.
[0145] (2) Dispersion of graphite flakes: First, take 3 pieces (11.75 g) of the treated cotton cloth and weigh 1.76 g of graphite flakes (particle size 10-20 μm, number of layers 1 to 10) according to the ratio of graphite flakes to the thermal conductive fabric of 15 wt%. Secondly, prepare a 2 wt% solution of PVA with polyvinyl alcohol (PVA) as a binder and water as a solvent. Finally, disperse a certain amount of graphite flakes in the PVA solution.
[0146] (3) Directed and orderly assembly of graphite layers on the surface of cotton cloth: the cotton cloth degreased in step (1) is immersed in the graphite flake suspension in step (2), and after repeated immersion, the graphite flakes are evenly dispersed on the cotton cloth.
[0147] The above steps can ensure that the graphite sheets are evenly dispersed on the cotton cloth to form a thermally conductive cloth.
[0148] (4) The thermal conductive fabric in step (3) is dried, and then sprayed with anhydrous ethanol to wet the thermal conductive fabric, and then the graphite sheet attached to the cotton cloth is rolled by a stainless steel cylinder to initially roll the graphite sheet into a continuous graphite layer. Finally, the thermal conductive fabric is replaced with a roller press for pressing.
[0149] 2. Preparation of directional heat conducting composite materials
[0150] First, cut 30 pieces of 5×5cm thermal conductive fabric from the pressed thermal conductive fabric, and brush bisphenol A epoxy resin glue on the surface of the thermal conductive fabric with a thickness of about 50μm. After the 30 pieces of thermal conductive fabric are adhered and stacked, they are pressed to form a layered porous directional thermal conductive substrate.
[0151] 3. Preparation of stearic acid phase change materials and oriented composite materials
[0152] 60g of stearic acid was placed in a beaker and heated to 100°C to completely melt it. Next, the directional heat-conducting composite material was immersed in liquid stearic acid to completely immerse it in the stearic acid, and then kept at a constant temperature of 80°C for 4 hours in a vacuum device, the sample was removed, and cooled to room temperature to obtain a directional phase change composite material.
Claims
1. A directional heat-conducting composite phase change material, characterized in that: It comprises a graphite layer, cotton cloth, an adhesive layer and a phase change material, wherein the cotton cloth is a cloth carrier impregnated with graphite flake powder; the graphite layer is symmetrically distributed on both sides of the cotton cloth, and the cotton cloth and the graphite layer constitute a thermally conductive cloth; the adhesive layer is evenly coated on both sides of the thermally conductive cloth, and a plurality of layers of thermally conductive cloth are adhered and stacked through the adhesive layer to form a porous directional thermally conductive matrix; The phase change material is impregnated in the above-mentioned directional porous thermal conductive matrix to form a directional thermal conductive composite phase change material; the thickness of the cotton cloth is 50 to 1000 μm, and its material is cotton cellulose or wood cellulose; the thickness of the graphite layer is 1 to 200 μm; the viscose is one of polyvinyl acetate emulsion, bisphenol A epoxy resin glue, acrylate glue, and polyurethane adhesive, and its thickness is 1 to 200 μm; the phase change material is one of higher aliphatic hydrocarbons, fatty acids, esters, and crystalline hydrated salts.
2. A directional heat-conducting composite phase change material according to claim 1, characterized in that: The preparation method comprises the following steps: (1) placing cotton in an alkaline solution and heating it for degreasing; (2) ultrasonically dispersing graphite flake powder in a predetermined binder solution to form a graphite flake suspension; (3) dipping the degreased cotton cloth in step (1) into the graphite flake suspension in step (2), and dipping the graphite flakes uniformly on the cotton cloth after repeated dipping. (4) After drying the cotton cloth with the graphite sheet attached in step (3), spraying anhydrous ethanol on the surface of the cotton cloth with the graphite sheet attached to wet it, and rolling it using a stainless steel roller and a roller press, so that the graphite sheet is closely attached to the cotton cloth, forming a graphite layer on both sides of the cotton cloth, and making a thermal conductive cloth; (5) applying adhesive to the surface of the heat-conducting fabric obtained in step (4), adhering and stacking several layers of the heat-conducting fabric, and pressing them to form a layered porous directional heat-conducting substrate; (6) Using a vacuum impregnation method, the phase change material is impregnated into the layered porous directional heat conducting matrix obtained in step (5) to obtain a composite phase change material having directional heat conducting properties.
3. The method for preparing a directional heat-conducting composite phase change material according to claim 2, characterized in that: The predetermined binder solution in step (2) is selected from one of the following binders dissolved in corresponding solvents, including dimethylacetamide as the corresponding solvent for polyvinylidene fluoride, dimethylformamide as the corresponding solvent for polyacrylonitrile, N-methylpyrrolidone as the corresponding solvent for polyamide, ethanol as the corresponding solvent for polyvinylpyrrolidone, ethanol as the corresponding solvent for polyacrylic acid, water as the corresponding solvent for sodium carboxymethyl cellulose, and water as the corresponding solvent for polyvinyl alcohol; the concentration of the binder solution is 1 to 5 wt%.
4. The method for preparing a directional heat-conducting composite phase change material according to claim 2, characterized in that: In step (3), the graphite sheet accounts for 15 to 50 wt % of the thermal conductive fabric.
Citation Information
Patent Citations
Production and installation method for graphite composite sheet
CN101488435A
Foam type thermal interface material with high thermal conductivity and preparation method of foam type thermal interface material
CN103589134A